Reduced hydrophobicity of the colonic mucosal surface in ulcerative colitis as a hint at a physicochemical barrier defect - Gauss, Annika; Schönfeld, Ulrike; Welsch, Thilo; Kadmon, Martina; Funke, Benjamin; Gotthardt, Daniel; Zahn, Alexandra; Autschbach, Frank; Kienle, Peter; Zharnikov, Michael; Grunze, Michael; Stremmel, Wolfgang; et al. (International journal of colorectal disease, 2011)
There is increasing evidence that a defect of the gastrointestinal mucosal barrier is important for the development of inflammatory bowel diseases (IBD). The hydrophobicity of the colonic mucosal surface is a measure of its resistance to luminal antigens, e.g. of bacterial origin. Therefore, the purpose of this study was to determine this parameter in patients suffering from IBD.
Gesehen am 03.06.2022